If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 + 2x + -1 = 6x + -20 Reorder the terms: 2 + -1 + 3x + 2x = 6x + -20 Combine like terms: 2 + -1 = 1 1 + 3x + 2x = 6x + -20 Combine like terms: 3x + 2x = 5x 1 + 5x = 6x + -20 Reorder the terms: 1 + 5x = -20 + 6x Solving 1 + 5x = -20 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 1 + 5x + -6x = -20 + 6x + -6x Combine like terms: 5x + -6x = -1x 1 + -1x = -20 + 6x + -6x Combine like terms: 6x + -6x = 0 1 + -1x = -20 + 0 1 + -1x = -20 Add '-1' to each side of the equation. 1 + -1 + -1x = -20 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = -20 + -1 -1x = -20 + -1 Combine like terms: -20 + -1 = -21 -1x = -21 Divide each side by '-1'. x = 21 Simplifying x = 21
| 35.8x+5.90=220.7 | | 17=6z-1 | | 36+(4x-9)=c(2x+1)+25 | | .666=3r | | 18x^2+18y^2-12x+9y+7=0 | | x^2-15x-15=-6x-5 | | -5+-16= | | 2b-8=0.4 | | (4x+7y)+(x-3y)= | | 5-2x=-5-x | | k+(4.21)=19.3 | | 13x+50=180 | | x^2-13x+28=-2x+4 | | -8=6b-14 | | 66.6=3r | | 3e=.75 | | x^2+13x+41=5 | | -(8y+5)-(-7y-7)=2 | | 2g-7g=-24 | | 6x+39=14x-66 | | -2(x-4)=12 | | 7x+3y=6x+5y | | -2(-2-4)=12 | | 6=4d-10 | | Y-4=7x(x-3) | | 5+5q=6+4q | | 6(2+-5)+5t=60-1 | | 11-j=2 | | 5+6=9+3 | | 18-13=m | | 2a+4b=30 | | 1.25=0.75r |